2018
DOI: 10.3201/eid2404.161977
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infections in Neonates, Madagascar, 2012–2014

Abstract: Severe bacterial infections are a leading cause of death among neonates in low-income countries, which harbor several factors leading to emergence and spread of multidrug-resistant bacteria. Low-income countries should prioritize interventions to decrease neonatal infections; however, data are scarce, specifically from the community. To assess incidence, etiologies, and antimicrobial drug–resistance patterns of neonatal infections, during 2012–2014, we conducted a community-based prospective investigation of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 24 publications
3
34
1
Order By: Relevance
“…All studies were hospital-based except for one community (home-based surveillance) study from Madagascar. 63 Hospital-based studies were mostly tertiary referral facilities (university or large national hospitals), and only 23 from district or secondary referral hospitals. 34,48,51,54,[59][60][61][62][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] 139 studies were in urban settings whereas others reported data from predominantly rural populations: five studies from Kenya, 54,61,64,65,68 three from Mozambique, 59,72,73 two from Nigeria, 79,80 and one from Cameroon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were hospital-based except for one community (home-based surveillance) study from Madagascar. 63 Hospital-based studies were mostly tertiary referral facilities (university or large national hospitals), and only 23 from district or secondary referral hospitals. 34,48,51,54,[59][60][61][62][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] 139 studies were in urban settings whereas others reported data from predominantly rural populations: five studies from Kenya, 54,61,64,65,68 three from Mozambique, 59,72,73 two from Nigeria, 79,80 and one from Cameroon.…”
Section: Resultsmentioning
confidence: 99%
“…77 88 studies involved prospective data collection, 61 were retrospective reviews (26 laboratory-based surveillance of aetiological data), and two studies had both retrospective and prospective components. There was one randomised trial, 28 one before-and-after study, 81 three case-control studies, 42,78,82 six observational cohort studies, 38,48,63,[83][84][85] and the remaining 139 studies were cross-sectional designs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also selected ESBL-producing E. coli from 88 recently pregnant healthy women living in Steung Meanchey and participating in the Bacterial Infections and antibiotic Resistant Diseases among Young children in low-income countries (BIRDY) program, a surveillance program of bacterial infections among young children in low- and middle-income countries ( 6 ). During September 2015–December 2016, ESBL-producing E. coli isolates were cultured from rectal swabs or fecal samples collected at or just after delivery (Appendix Table 3).…”
Section: The Studymentioning
confidence: 99%